Importance of phytotherapy for oral health care and quality of life in adults: A scoping review - Rosemary Sadami Arai Shinkai; Camila Lindoni Azevedo; Tomie Toyota de Campos; Edgard Michel-Crosato; Maria Gabriela Haye Biazevic (Elsevier, 2024)
Medicinal plants and herbal medicines are used as integrative and complementary practices to provide comprehensive care, disease prevention, health promotion, and to improve quality of life (QoL). This scoping review aimed to identify and describe the use of phytotherapy in oral health care by adults and their outcomes, with a focus on perceptions of oral health-related QoL, healthcare access, and costs. A systematic search was conducted in six databases and supplemented in grey literature. According to a PRISMA-ScR protocol and eligibility criteria, publications were assessed for final inclusion, data charting, and narrative synthesis. Out of 4124 records, 542 publications were selected for full-text reading. A total of 32 studies were included: 21 studies assessed QoL, 7 reported access issues, and 11 reported costs issues. Herbal mouthwashes to prevent or treat non-infectious oral conditions were the most frequent treatment. Efficacy of phytotherapy was usually better than placebo or control treatment. Most studies reported QoL improvement, but several instruments were used with heterogeneous results. Limited healthcare access and high costs favoured traditional folk herbal medicine in underserved populations. It can be concluded that phytotherapy for oral health is used by adults worldwide, following modern clinical pharmacology and traditional knowledge concepts. Further studies should incorporate assessment of QoL, access, and costs in addition to clinical efficacy and safety, which are complementary aspects for delivering a comprehensive and efficient health care for all people.